Stable complex formation of thylakoidal processing peptidase and PGRL1. Issue 14 (31st May 2013) - Endow, Joshua K.; Inoue, Kentaro
Abstract : The thylakoid‐transfer signal is required for energy‐dependent translocation of preproteins into the thylakoid lumen and is removed by the thylakoidal processing peptidase (TPP). PGRL1 is an essential component of antimycin A‐sensitive photosynthetic cyclic electron flow in chloroplasts. Here we report that one of the TPP isoforms, Plsp1, forms a stable complex with PGRL1. Genetic data demonstrate that PGRL1 is not essential for Plsp1 activity in vivo, leading to a possibility that PGRL1 may act as a regulator of TPP. Abstract : The two thylakoidal processing peptidase isoforms are present in distinct complexes. Plsp1 and PGRL1 form a stable complex. The complex with PGRL is dispensable for the known functions of Plsp1in vivo.